Externalities, Social Value and Word of Mouth: Notions of Public Economics on Networks - Pier-André Bouchard St-Amant (Queen's University, Department of Economics, 2013)
I examine an environment where advertisers can 'seed' word-of-mouth advertising by providing initial information about a product to specific users of a social network. Discussion over a social network generates spillover effects for firms when consumers can use the social network to inform each other about products. When a firm can exploit a social network's structure, it can increase its sales. However, when the network formation process is costly, firms free-ride on such costs at the expense of agents on the network. If agents can form coalitions, I show that they can recoup the value of this externality by charging a toll. When users actively modify the information, generating word-of-mouth advertising about a product provides a 'social value'. This social value stems from the discussions that agents have about the product, without any intervention. Since this process occurs regardless of the firm's actions, the firm cannot capture such valuation. The opinion leaders, or highly regarded agents on the network, play a key role in the formation of this social value.
Keywords: D83; D85; 330; network; word of mouth; externalities; social value